Ovarian function and ovarian blood supply following premenopausal abdominal hysterectomy - Abdelazim, Ibrahim A.; Abdelrazak, Khaled M.; Elbiaa, Assem A.M.; Farghali, Mohamed M.; Essam, Amr; Zhurabekova, Gulmira (Menopause Review/Przegląd Menopauzalny, 2015)
Introduction: The issue of conserving the ovaries at hysterectomy in premenopausal women with benign gynecologic disease has been the subject of considerable controversy. Some clinicians prefer prophylactic oophorectomy in premenopausal women during hysterectomy to prevent future development of malignant changes in conserved ovaries. Other clinicians prefer to conserve apparently normal ovaries, because bilateral oophorectomy in premenopausal women results in an abrupt imbalance, sudden onset of menopausal symptoms, decreased libido, increased cardiovascular risk and osteoporosis. Material and methods: Two hundred and twenty multipara women (who had completed their families), with benign uterine pathology were included in this prospective study for abdominal hysterectomy with bilateral ovarian preservation. Pre-operative vaginal ultrasound, Doppler studies, diagnostic hysteroscopy and endometrial biopsy were done followed by laboratory studies including Anti-mullerian hormone (AMH), follicle stimulating hormone (FSH) and estradiol for all studied women. Doppler studies, AMH, FSH and estradiol were repeated 6 and 12 months post-operative for assessment of the ovarian function and ovarian blood supply after hysterectomy. Results : Pre-operative AMH, FSH and estradiol of the studied women were statistically insignificant compared to AMH, FSH and estradiol 6 and 12 months post-operative. Twelve months post-operative right and left ovarian volumes (6.92 ± 0.18 and 6.85 ± 0.19 cm 3 , respectively) were significantly larger than pre-operative right and left ovarian volumes (6.19 ± 0.22 and 5.86 ± 0.23 cm 3 , respectively), and, 12 months post-operative right and left ovarian pulsatility indices (2.92 ± 0.15 and 2.96 ± 0.16 cm/s, respectively) were significantly lower than pre-operative right and left ovarian pulsatility indices (3.45 ± 0.19 and 3.36 ± 0.2 cm/s, respectively). Eight (3.6%) cases of the studied women developed an ovarian cyst 6 months after hysterectomy, 3 were spontaneously resolved and the remaining 5 (2.27%) cases underwent exploratory laparotomy. Conclusions : There is no evidence of ovarian dysfunction affecting conserved ovaries one year after hysterectomy in premenopausal women as evident by AMH, FSH and estradiol. Furthermore, an increased ovarian volume and reduced ovarian pulsatility indices indicate a possible increase in ovarian blood supply, and preserved non-compromised ovarian function.